Паліндромічні словесні іграшки в контексті українського літературного бароко XVII-XVIII століть (спроба проекції на сьогодення) - Бойко, С. (Літературознавчі обрії. Праці молодих учених, 2010)
The investigation of the old Ukrainian palyndromous poetry of the XVII−XVIII centuries in its projection onto Ukrainian literature of the XX century (e.g. futurism) and its ancient origins was performed in the given work.